2011
DOI: 10.1186/1752-1947-5-252
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced hemorrhagic gastric ulcer after successful Helicobacter pylori eradication: two case reports

Abstract: IntroductionHelicobacter pylori infection is a major cause of gastric ulcers, and Helicobacter pylori eradication drastically reduces ulcer recurrence. It has been reported, however, that severe physical stress is closely associated with gastric ulceration even in Helicobacter pylori -negative patients.Case presentationWe report the cases of a 47-year-old Japanese man and a 69-year-old Japanese man who developed psychological stress-induced hemorrhagic gastric ulcers, in both of whom Helicobacter pylori had be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
1
6
0
1
Order By: Relevance
“…Xia et al 35 have shown that 17% of duodenal ulcers were H. pylori-and NSAID-negative and revealed that the presence of concomitant diseases was an independent predictor for those ulcers. Some other studies gave the same results [36][37][38] . Na et al 39 compared geriatric (older than 65) and non-geriatric patients with peptic ulcer bleeding and found that there was no difference in the incidence of H. pylori negative ulcers between compared groups.…”
Section: Discussionsupporting
confidence: 72%
“…Xia et al 35 have shown that 17% of duodenal ulcers were H. pylori-and NSAID-negative and revealed that the presence of concomitant diseases was an independent predictor for those ulcers. Some other studies gave the same results [36][37][38] . Na et al 39 compared geriatric (older than 65) and non-geriatric patients with peptic ulcer bleeding and found that there was no difference in the incidence of H. pylori negative ulcers between compared groups.…”
Section: Discussionsupporting
confidence: 72%
“…Stress ulcers differ from ordinary peptic ulcers in risk factors and symptoms. There are strong suggestions that not only physical but also psychological stress is an important pathogenic factor for gastric ulceration [5]. Insufficient blood microcirculation in the upper gastro intestinal tissues is considered as the major cause of mucosal defence reduction leading to the ulcer formation.…”
Section: Introductionmentioning
confidence: 99%
“…Stress ulcers are one of the most common stress-related disorders that affect the digestive system (Zhang et al, 2012). Severe physical stress is closely associated with gastric ulceration, even in Helicobacter pylori-negative patients (Moriya et al, 2011). Therefore, other factors apart from H. pylori, particularly stress, must be considered in the etiology and treatment of peptic ulcers.…”
Section: Introductionmentioning
confidence: 99%